2015
DOI: 10.18608/jla.2015.21.5
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Effects of Metacognitive Prompts on the Sequential Structure of SRL-Processes Using Process Mining Techniques

Abstract: According to research examining self-regulated learning (SRL), we regard individual regulation as a specific sequence of regulatory activities. Ideally, students perform various learning activities, such as analyzing, monitoring, and evaluating cognitive and motivational aspects during learning. Metacognitive prompts can foster SRL by inducing regulatory activities, which, in turn, improve the learning outcome. However, the specific effects of metacognitive support on the dynamic characteristics of SRL are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…As such, it appears that the provided structure affected the reading and writing patterns of the participants. This finding is coherent with research on SRL, which showed that interventions that aided regulation by means of prompts, changed the learning process of the learners (Sonnenberg & Bannert, 2015). Furthermore, prior research has shown that advance organizers, which provide structure to the learning content, can aid learners navigation and comprehension on the Internet (Urakami & Krems, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As such, it appears that the provided structure affected the reading and writing patterns of the participants. This finding is coherent with research on SRL, which showed that interventions that aided regulation by means of prompts, changed the learning process of the learners (Sonnenberg & Bannert, 2015). Furthermore, prior research has shown that advance organizers, which provide structure to the learning content, can aid learners navigation and comprehension on the Internet (Urakami & Krems, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…At the macro-level, several studies have shown that different learning processes can be observed in (groups of) learners who learn under different task conditions (Bannert, Reimann, & Sonnenberg, 2014;Sobocinski, Malmberg, & Järvelä, 2017;Sonnenberg & Bannert, 2015), or who have different learning outcomes (Schoor & Bannert, 2012). As learners gain experience in a task, they may approach the task differently (see e.g., expertise reversal effect; Kalyuga et al, 2003).…”
Section: Macro-level Navigation Patternsmentioning
confidence: 99%
“…This is the primary rationale for fostering teachers’ self‐regulation in technology integration contexts. Theories of self‐regulation affirm that self‐regulated learners are more adaptive in identifying and deploying effective strategies for problems and evaluating their effectiveness to guarantee outstanding performances (eg, Bannert et al ., 2015; Sonnenberg & Bannert, 2015; Taub & Azevedo, 2018; Zhou & Winne, 2012; Zimmerman, 1986). Integrating different types of technologies into teaching is trendy for future education.…”
Section: Discussionmentioning
confidence: 99%
“…To check the behaviour proportion on event logs in the model, the fitness significance is calculated (defined in Kurniati, Kusuma, & Wisudawan, 2016;Sonnenberg & Bannert, 2015) using the following formula:…”
Section: Process Miningmentioning
confidence: 99%